The Role of Education Quality Management in Improving Qur'any Literacy Culture - Sukaisih, Tin; Widayatsih, Tri; Fitriani, Yessi (Journal of Social Work and Science Education, 2021)
The importance of education quality management in improving the culture of qur'any literacy at Miftahul Ulum Makarti Jaya Islamic School is described in this qualitative research. According to the study's findings, education quality management has a role in producing superior output generation that is inventive, critical, leadership, and creative superior and able to compete well and have more value in religious abilities. Being cultural and literate, as well as critical thinking, are two qualities that can develop outputs that are ready to participate in society.